Adult female survival, reproductive success, and breeding habitat relationships of wild turkeys (Meleagris gallopavo) across a precipitation gradient in Kansas - Skidmore, Caroline K. (My University, 2026)
The reintroduction of wild turkey (Meleagris gallopavo) populations across the United States is a conservation success story. Their recovery during the past 75 years was the result of widespread relocations throughout the eastern and Midwest United States beginning in the 1950s, finally reaching an abundance level to open spring hunting season in Kansas in 1974. However, there is now a suspected near-nationwide population decline for wild turkeys, including Kansas, starting in the mid-2000s in the eastern United States that is progressing westward with severity varying among states. Initial responses to these declines include increasingly smaller bag limits and cancelled hunting seasons, which detrimentally affect state wildlife agencies on economic, cultural, and sociologic levels. To investigate potential factors influencing the demography of wild turkey populations, I captured and marked 297 and 102 female wild turkeys in 2024 and 2025, respectively, using G5-T2A Iridium backpack style transmitters. I remotely monitored the movements of each female weekly during the breeding season to monitor for indications of the bird entering the laying, incubating, or brood-rearing states. When a female successfully incubated a nest, I completed weekly brood flush counts to determine poult survival up to 28 days following hatch. I conducted habitat surveys at used and randomly available nesting and brood-rearing locations to test for resource selection and record potential factors affecting nest, brood, and adult female survival. Nest-site use across a landscape was best predicted by tree distribution, specifically within a maximum proximity of 286 m and a mean proximity of use at ~34 m, but nests were primarily placed within grassland landcover patches (>70% of nests). At a fine-scale, visual obstruction and woody composition were most influential for modeling nest-site use by wild turkeys; both increasing the probability of nest-site use. Nest survival estimates were similar between survey years, at a realized nest survival for a 28 day incubation period of 0.17 ± 0.05 in 2024 and 0.15 ± 0.05 in 2025. Private lands had the same estimated nest success (Ŝ = 17.45% ± 4.0) as public lands (Ŝ = 17.28% ± 7.00). Adult females (≥2 years old at time of nesting) had a slightly greater but insignificantly different nest survival estimate (Ŝ = 17.78% ± 4.0) than juvenile females (Ŝ = 15.49% ± 8.14). Despite not being selected, mean forb composition at 10 m around the nest negatively affected nest daily survival rate ([beta] = -0.0085 ± 0.003, LCL = -0.0141, UCL = -0.0029). Forb composition was ubiquitous among used habitats of both brood-rearing and nesting wild turkeys, possibly indicating areas available for nesting incur disturbance levels detrimental to nest success but beneficial to brood survival. Apparent survival of broods in Kansas was 33% in 2024, and 22% in 2025; Poult survival increased with each week following hatch, starting at 0.53 ± 0.03 (LCL = 0.465, UCL = 0.592) in week one, 0.59 ± 0.04 (LCL = 0.514, UCL = 0.670) in week two, 0.95 ± 0.04 (LCL = 0.755, UCL = 0.992) in week three, and finally 1.00 ± 0.00 in weeks four and five. I estimated laying phase core ranges of females with successful nests to investigate if pre-brood rearing behaviors impacted subsequent poult survival. The laying period core range negatively affected 0–14-day poult survival; At the smallest recorded laying core home range of a brood rearing female, 2.70 ha, poult survival for the first two weeks of life is estimated to be 0.62 ± 0.017 (LCL= 0.589, UCL = 0.655). By the third quantile of core area, 157.13 ha, poult survival decreased by 19% to 0.43 ± 0.048 (LCL = 0.342, UCL = 0.530). Lastly, cumulative, 52-week survival of female wild turkeys was 52.10% ± 3.1 (LCL = 46.4%, UCL = 58.5%) in 2024 and 46.4% ± 3.3 (LCL = 41.2%, UCL = 54.3%) in 2025. Female wild turkey survival was lowest in the reproductive period, during which 79.4% of all mortalities occurred. Survival of wild turkey females was 49.53% ± 0.001 during the reproductive period and 82.70% ± 0.001 during the non-breeding period. Despite wild turkeys being distributed across an expansive precipitation and resource gradient from east to west, female wild turkey survival did not differ among study regions or hunting management units. For example, the 30 year mean annual precipitation of the western study region was 9.61 cm ± 15.74 SD, while the 30 year mean annual precipitation of the eastern study region was 14.31 cm ± 23.16 SD. Furthermore, of the variables measured, nest habitat (nest visual obstruction up to 50 cm at the nest bowl, woody composition at the nest bowl, forb composition at a 10 m radius around the nest, and visual obstruction up to 50 cm at a 10 m radius around the nest) had no effect on female wild turkey survival during the reproductive period. Apparent wild turkey nest success values in 2024-2025 (4-30%) among study sites fall slightly below that of pre-2004 (8-54%) apparent nest success for the Great Plains region and appears to regularly entail large variation among study sites, both historically and present-day. Poult survival was similar to that of previous studies (40-52%), although limited references are available pre-2004. Finally, annual survival of female wild turkeys in Kansas falls below a 68% model-averaged female survival estimate preceding the nationwide population decline starting in 2004 published by Lashley et al. (2025). Based on these results, reproductive vital rates support signs of a more limited population trajectory in comparison to the near 50-year population increase following reintroduction. Because both nesting and brood-rearing success suffer from female-specific mortality rather than general failure, adult female wild turkey survival is the most probable origin of the resulting decline.
Keywords: Wildlife conservation and biology; Known fate; Breeding ecology; Great Plains ecoregion; Game bird management